Cork-Containing Barks—A Review - Leite, Carla; Pereira, Helena (Frontiers in Materials, 2017)
Tree barks are among the less studied forest products notwithstanding their relevant physiological and protective role in tree functioning. The large diversity in structure and chemical composition of barks makes them a particularly interesting potential source of chemicals and bio-products, at present valued in the context of biorefineries. One of the valuable components of barks is cork (phellem in anatomy) due to a rather unique set of properties and composition. Cork from the cork oak (Quercus suber) has been extensively studied, mostly because of its economic importance and worldwide utilization of cork products. However, several other species have barks with substantial cork amounts that may constitute additional resources for cork-based bioproducts. This paper makes a review of the tree species that have barks with significant proportion of cork and on the available information regarding their bark structural and chemical characterization. A general integrative appraisal of the formation and types of barks and of cork development is also given. The knowledge gaps and the potential interesting research lines are identified and discussed, as well as the utilization perspectives.